Le traducteur et son image. Étude des couvertures d’ouvrages de traductologie - Skibińska, Elżbieta (Studia Romanica Posnaniensia, 2021)
The front cover of a book usually contains the title, the authors’names, the publisher’s logo and an illustration. All these elements announce the content of the book, and the paraverbal elements (illustration, typographical arrangement…) can also be used to awaken the curiosity of the potential reader. This article deals with the reproductions of art works chosen by the editors for the front covers of Translation Studies books. Cover illustrations are treated here as a kind of “definition of translator’s work through a pictorial metaphor”, i.e. as a representation of how translation can be understood or as an indication of its important features. The analysis of these illustrations shows the various means used by the publishers of Translation Studies books to define translation through pictures.